GAYA KEPEMIMPINAN, SISTEM PENGENDALIAN INTERNAL PEMERINTAH, DAN TEKNOLOGI INFORMASI PADA KUALITAS LAPORAN KEUANGAN PEMERINTAH DAERAH - Yanti, Ni Wayan Rita Ardina; Rasmini, Ni Ketut (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2024)
The increasing demand for accountability and transparency in regional finances along with the development of the public sector in Indonesia, requires the submission of quality financial reports. This research aims to examine the influence of leadership style, the government's internal control system, and the use of information technology on the quality of the Badung Regency regional government's financial reports. Research data was collected through questionnaires given to 80 financial employees of regional apparatus organizations in Badung Regency using purposive sampling techniques. Data analysis was carried out using the SEM-based PLS method using SmartPLS. The research results show that leadership style, the government's internal control system, and the use of information technology have a positive and significant influence on the quality of the Badung Regency regional government's financial reports. Theoretically, this research contributes to the implementation of agency theory and acceptance theory and the use of technology in regional financial management. Practically, the results of this research can be used as input and evaluation material for the Badung Regency Government or other regional governments regarding the factors that need to be considered to produce quality regional government financial reports that are able to meet the financial information needs of their users.